2007
DOI: 10.1111/j.1469-8137.2007.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of isoprene emission and carbon metabolism to drought in white poplar (Populus alba) saplings

Abstract: Summary• The mechanism uncoupling isoprene emission and photosynthesis under drought was investigated in Populus alba saplings.• Isoprene emission, incorporation of 13 C into the isoprene molecule, isoprene synthase (ISPS) activity, concentration and gene expression, and photosynthesis were measured as a function of the fraction of transpirable soil water (FTSW) and in plants recovering from drought.• Photosynthesis sharply declined below FTSW 30 (a FTSW of 30%) and its inhibition was not caused by metabolic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
268
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(299 citation statements)
references
References 54 publications
(102 reference statements)
28
268
2
1
Order By: Relevance
“…It has been proposed that leaf isoprene emission is an important adaptation for plants, conferring tolerance to different environmental constraints (Vickers et al, 2009;Loreto and Schnitzler, 2010;Loreto and Fineschi, 2014). However, biogenic isoprene emission represents a nontrivial carbon loss in plants, particularly under stress conditions (Fang et al, 1996;Brilli et al, 2007;Teuber et al, 2008;Ghirardo et al, 2014), and the reason(s) why plants emit isoprene are still ambiguous, and the true role of isoprene emission remains elusive. Different approaches and techniques have been used to determine whether and how the cost of this expensive carbon emission is matched by the accomplishment of the physiological function in planta.…”
mentioning
confidence: 99%
“…It has been proposed that leaf isoprene emission is an important adaptation for plants, conferring tolerance to different environmental constraints (Vickers et al, 2009;Loreto and Schnitzler, 2010;Loreto and Fineschi, 2014). However, biogenic isoprene emission represents a nontrivial carbon loss in plants, particularly under stress conditions (Fang et al, 1996;Brilli et al, 2007;Teuber et al, 2008;Ghirardo et al, 2014), and the reason(s) why plants emit isoprene are still ambiguous, and the true role of isoprene emission remains elusive. Different approaches and techniques have been used to determine whether and how the cost of this expensive carbon emission is matched by the accomplishment of the physiological function in planta.…”
mentioning
confidence: 99%
“…Although the disconnection between photosynthesis and VTC emission has been reported, the crucial requirement of photosynthetic carbon in the biosynthesis of VTCs has also been acknowledged [35], suggesting the possibility of alternative sources of carbon for VTC synthesis. Although not fully identified and understood, in recent years labelling studies have suggested that xylem-transported carbon and chloroplast starch may be alternative sources of carbon for VTCs biosynthesis [10] [11]. It is expected that during abiotic stress related senescence where there is colossal depletion of plant starch, VTC biosynthesis will cease, however the contrary has been reported and speculating that extra-chloroplastic sources of carbon may be activated and feed carbon to stimulate VTCs biosynthesis [11].…”
Section: Stress Senescence and The Role Of Vtcsmentioning
confidence: 93%
“…The maintenance of high levels of isoprene emission, contributed by an increasingly large fraction of the carbon fixed by photosynthesis, is an indirect evidence of the importance of isoprene in protecting poplars against abiotic stresses, such as water stress (e.g., Brilli et al 2007), ozone stress (Fares et al 2006) and Ni stress (Velikova et al 2011). These findings are likely to be relevant for process-based models that account for stress effects in order to predict the emissions of isoprenoid in globally changing environmental conditions, as well as the sensitivity to high UV-A (Pallozzi et al 2012), and to scale up the impact of isoprenoid on air chemistry and quality at regional and global levels (Brilli et al 2007). Pellegrino et al (2011) have observed the important role of plant-soil interactions under different harvest intensity in sustainable bioenergy crop management, with improved soil quality in poplar plantations (short rotation forestry, SRF) in comparison with intensive cropping systems.…”
Section: Restoration Ecology With Fast Growing Treesmentioning
confidence: 99%